Pengaruh Kecerdasan Emosional Dan Sikap Kerja Terhadap Kinerja Pegawai Pada Badan Pendapatan Daerah Kabupaten Sikka - Ermelinda Beatriks Kewa; Walter Obon; Yustina Olivia Da Silva (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
The Background of this research was to (1) grasp the representation of employee performance, emotional intelligence, and work attitude;(2) analyze the influence of emotional intelligence, and work attitude on employee performance partially or simultaneously. The population in this research was employee of Local Government Revenue Agency of Sikka Regency as many as of 57 people. The research was conducted by census or saturated sampling due to to limited population. Data were collected through questioner and analysed with descriptive and statistic inferential methods that was multiple regression linear. The hypothesis was done through F-test and t-test. The result of descriptive analysis showed that the variables of employee performance, emotional intelligence, and work attitude were categorized as good. The result of the statistic t-test showed that partially the variable of emotional intelligence, and work attitude had a positive impact on employee performance. The statistic F-test showed that simultaneously the variable of emotional intelligence, and work attitude significantly affected employee performance. The result of the determination showed that both independent variables in this research could enlighten the fluctuation of employee at the Local Government Revenue Agency of Sikka Regency of 22,16%.